Microcharcoal analysis of surface ocean sediments offshore Africa - Aritina Haliuc; Anne-Laure Daniau; Florent Mouillot; Wentao Chen; Bérangère Leys; Valérie David; Vincent Hanquiez; Bernard Dennielou; Enno Schefuß; Germain Bayon; Xavier Crosta (PANGAEA, 2025)
Microscopic charcoal (microcharcoal) was analysed in 128 samples recovered from surface ocean sediments offshore Africa and compared with fire regimes on land to evaluate the potential of microcharcoal (amount and morphology) to reconstruct fire regime characteristics. Microcharcoal concentrates were obtained after chemical treatment and microcharcoal was measured using microscopy The dataset presents for each sample microcharcoal concentration (in number of fragments per gram and in μm^2 per gram); mean area of microcharcoal (μ^2); mean length and mean width of the particles (μm^2); and the mean microcharcoal elongation ratio (the length to width ratio of particle). The dataset is presented along with metadata information on the marine surface sediment samples including the method collection, geographic information, water depth of the core, the associated hydrographic basin on land, and information relevant to infer an estimated time interval covered by a sample (such as the sedimentation rate, dating information, depositional context).